2020
DOI: 10.1002/bco2.63
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of hydrophilic‐coated urinary catheters for individuals with spinal cord injury: A systematic review

Abstract: A large proportion of individuals with spinal cord injuries suffer from neurogenic bladder. In the United States, neurogenic bladder affects 80% of the 12 000 patients with new spinal cord injuries per year. 1,2 Of these individuals, more than 80% will need some form of urinary catheterization. 3 Individuals requiring catheterization have several options broadly falling into two categories: indwelling and intermittent catheters. Indwelling catheters are inserted via the urethra or the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…For the selection of an appropriate intermittent catheter, it is recommended to use hydrophilic‐coated catheters. Research has shown that hydrophilic‐coated catheters are not only conducive to preventing complications but also are more cost‐effective (Xi et al., 2021 ). During intermittent catheterization, patients should be instructed to carefully implement a drinking water plan and maintain a urination diary, as well as adjust the frequency of intermittent catheterization based on their residual urine volume (Fang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the selection of an appropriate intermittent catheter, it is recommended to use hydrophilic‐coated catheters. Research has shown that hydrophilic‐coated catheters are not only conducive to preventing complications but also are more cost‐effective (Xi et al., 2021 ). During intermittent catheterization, patients should be instructed to carefully implement a drinking water plan and maintain a urination diary, as well as adjust the frequency of intermittent catheterization based on their residual urine volume (Fang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Have a look at their use of “meaning extraction method” and see if it may give you ideas for your own future studies. To the Journals… The review by Xi et al 4 is a systematic methods effort that focused on the question of whether or not hydrophilic‐coated versus standard catheters are cost‐effective in spinal cord injury patients. Of eight studies that passed eligibility, five supported hydrophilic‐coating, and the authors dive into the details of the conflicting results with an overall favourable rating of the cost‐effective and quality of life merits.…”
mentioning
confidence: 99%